Reduced survival in a soaring bird breeding in wind turbine proximity along the northern Baltic Sea coast - Nebel, Carina; Stjernberg, Torsten; Tikkanen, Hannu; Laaksonen, Toni (Elsevier, 2025)
Wind power plays a vital role in global climate action and plans for new turbines in the Baltic Sea region are underway. However, it is crucial not to overlook the environmental impact on wildlife, which can be difficult to quantify, especially in elusive and hard-to-track species. One of these species is the white-tailed eagle, a conservation success story that faces a significant collision risk with rotor blades, particularly as turbines are being constructed in its coastal habitats. To assess the effect of wind turbines on survival of territorial adults, we genotyped DNA from adult feathers collected at nests between 2010 and 2022. By tracking individuals across years, we measured survival and breeding dispersal in relation to wind turbine presence. Turbines within a 5 km radius of nests were found to reduce annual survival rates by 7.6 %, while resighting probability and breeding dispersal probability were unaffected. The proportion of territories exposed to wind turbines is currently low (4–5 %), mainly because recent construction sites have been further inland. However, future projections suggest an increase in territory exposure, indicating potential for population-level risks. This highlights the need for substantial safety buffers around nest sites (preferably >5 km) to protect the breeding white-tailed eagle population. Currently, a comprehensive understanding of the large-scale impact on the Baltic Sea white-tailed eagle population is lacking. As wind power expands, it is necessary to consider its impact on wildlife and we recommend conducting ongoing environmental assessments to monitor and adapt conservation measures.